MORPHOLOGICAL COMPARISON OF NUMERAL SYSTEMS IN INDONESIAN AND TAGALOG: AUSTRONESIAN ROOTS AND COLONIAL INFLUENCES - Aqromi, Nur Lailatul; Espejo, Rommel V (Laboratorium Informasi & Publikasi Fakultas Humaniora UIN Maulana Malik Ibrahim Malang, 2024)
Numeral systems are essential for understanding the structure and evolution of languages, as they reflect cognitive processes and are deeply shaped by historical and cultural influences. This study examines the numeral systems of Indonesian and Tagalog, two Austronesian languages, focusing on the morphological processes involved in numeral formation. Despite sharing a common linguistic ancestry, the numeral systems of these languages differ significantly due to various historical and cultural factors, including the impacts of colonization. The research employs a descriptive-qualitative approach, utilizing contrastive analysis to compare the morphological structures of numerals in both languages. Data were collected from literary texts, dictionaries, and language corpora in both languages, and the analysis involved distributional, comparative, and contextual methods. Additionally, consultations with native speakers helped verify numeral usage and clarify any ambiguities. Findings reveal that while both languages use a decimal numeral system, Indonesian generally employs simpler affixation patterns, such as the prefix